Perancangan E-commerce Website Asy-Syifa CARE Menggunakan Framework PHP: CodeIgniter - Muhammad Farras Muttaqin; Muhammad Fadzly Yusuf; Mochammad Gatot Subroto (JURNAL TEKNIK KOMPUTER, 2019)
Problems regarding health complaints and community needs for herbal medicines always increasing in every year. The purpose of this research is to implement the Asy-Syifa CARE’s e-commerce website which has a function as a media for promotion and selling of herbal medicines by online way. This research took a case on Asy-Syifa CARE startup, by collecting data through the secondary data sources. Data collection techniques carried out by the author is using literature studies on scientific journals related to e-commerce websites as a media for product promotion and sales. The results of this research is an e-commerce website using framework CodeIgniter version 3.1.9 that uses the MVC programming concept (Model-controller-view). Expectations from the results of this research is can helping Asy-Syifa CARE startup in improve the quality of their product branding in digital marketing, so they able to increase the revenue statistics and be able to compete with another e-commerce website competitors.